Peran Kepolisian Dalam Penegakan Hukum Tindak Pidana Menguasai Lahan Perkebunan di Wilayah Hukum Polres Langkat - Kusuma, Juanda; Warman, Edi; Siregar, Taufik (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The purpose of this paper is to examine and analyze the rule of law, the role of the Langkat Police and its obstacles regarding the crime of plantation land in the Langkat Police Legal Area. The research method uses normative juridical research by analyzing legislation and conceptual analysis with descriptive data analysis. The results of this study indicate that the rule of law regarding control of plantation land is regulated in the provisions of Law no. 39 of 2014 concerning Plantations, where the threat of imprisonment is regulated in the provisions of Article 107 is sentenced to a maximum imprisonment of 4 years or a maximum fine of 4,000,000,000 (four billion rupiah), the role played by the Langkat Police in law enforcement of the crime of controlling plantation land namely referring to Law no. 2 of 2002 concerning the Police, and the obstacles faced by the Langkat Police in law enforcement of the crime of controlling plantation land, which consist of obstacles from the rule of law, obstacles from law enforcement, and obstacles from facilities and infrastructure.